The labor market consequences of political imprisonment in the former GDR - Nicole Gürtzgen; Karsten Hank (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Barely any quantitative research has been devoted yet to the labor market consequences of incarceration for political offenses, which seems particularly unfortunate against the background of Europe's history of state persecution in the 20th century. Drawing on the example of the former German Democratic Republic (GDR), our paper seeks to gain a deeper understanding of how the experience of political imprisonment affected individuals subsequent career outcomes. In our empirical analysis, we exploit a one-percent sample drawn from a unique large-scale administrative data set (BASiD). To the best of our knowledge, our study provides unprecedented evidence on the labor market effects of political imprisonment, by (1) exploiting information on political imprisonment using administrative records; (2) differentiating between possible short and long-run consequences of political imprisonment; and (3) measuring outcomes before and after the transition from a centrally planned towards a market economy, thereby permitting us to distinguish the consequences of incarceration under different political and economic regimes.
Keywords: J15; K40; P37; 330